The anthropology of sport : bodies, borders, biopolitics - Besnier, Niko; Brownell, Susan; Carter, Thomas F., 1967- (University of California Press, 2018)
"Few activities bring together physicality, emotions, politics, money, and morality as dramatically as sport. In Brazil's stadiums or parks in China, on Cuba's baseball diamonds or rugby fields in Fiji, human beings test their physical limits, invest emotional energy, bet money, perform witchcraft, and ingest substances, making sport a microcosm of what life is about. The Anthropology of Sport explores not only what anthropological thinking tells us about sports, but also what sports tell us about the ways in which the sporting body is shaped by and shapes the social, cultural, political, and historical contexts in which we live. Core themes discussed in this book include the body, modernity, nationalism, the state, citizenship, transnationalism, globalization, and gender and sexuality"--Provided by publisher.